2018
DOI: 10.4012/dmj.2017-294
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and dentin bonding ability of combined use of Clearfil SE Protect and sodium hypochlorite

Abstract: The aim of this study was to evaluate the antibacterial activity and dentin bonding ability of a commercial self-etch adhesive Clearfil SE Protect (Kuraray Noritake Dental, Tokyo, Japan) in combination with sodium hypochlorite (NaOCl). Agar disc diffusion tests and measurement of minimum inhibitory/bactericidal concentrations (MIC/MBC) against Streptococcus mutans were performed to evaluate antibacterial effects. The mixture solution of 5.25% NaOCl and the primer of Clearfil SE Protect demonstrated less antiba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
(27 reference statements)
0
6
0
3
Order By: Relevance
“…These results echo the ones found in a study which also assessed the durability of CFP and found it to be stable over time [ 68 ]. Apparently, this group was less vulnerable to a hybrid layer breakdown, which is pointed out in the literature [ 15 , 23 , 50 , 54 ]. The accepted theory for this trend seems to be linked to 12-MDPB’s QAC group, which may be able to inhibit matrix metalloproteinases (MMPs) and thus, protect the hybrid layer, as previously investigated by Almahdy et al (2012), Tezvergil-Mutluay et al (2015), and Liu et al (2011) [ 23 , 32 , 69 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These results echo the ones found in a study which also assessed the durability of CFP and found it to be stable over time [ 68 ]. Apparently, this group was less vulnerable to a hybrid layer breakdown, which is pointed out in the literature [ 15 , 23 , 50 , 54 ]. The accepted theory for this trend seems to be linked to 12-MDPB’s QAC group, which may be able to inhibit matrix metalloproteinases (MMPs) and thus, protect the hybrid layer, as previously investigated by Almahdy et al (2012), Tezvergil-Mutluay et al (2015), and Liu et al (2011) [ 23 , 32 , 69 ].…”
Section: Discussionmentioning
confidence: 65%
“…Given their respective composition, Clearfil SE Bond 2 is thus the ideal control when testing Clearfil SE Protect. 12-MDPB is described as a powerful antibacterial agent, able to co-polymerize within the organic matrix to other monomers [ 24 , 51 , 52 , 53 ], and provide an inhibitory action against oral Streptococci, without compromising the quality of the adhesive interface [ 15 , 23 , 50 , 54 ]. This antibacterial action has proven to be a promising strategy regarding treatment longevity, as proposed by Hashimoto et al (2018) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Having dental adhesives with antibacterial properties is a viable option to suppress the bacterial colonization around restorations and prevent the replacement of restorations due to recurrence of caries. Some commercially available dental adhesives are modified by the inclusion of antibacterial agents such as glutraldehyde (eg, Gluma 2 Bond) (25), chlorhexidine (eg, Peak Universal Bond) (26) and methacryloyloxydodecylpyridinium bromide (MDPB) (eg, Clearfile SE Protect) (27). Regardless of the antibacterial action of these adhesives, none of them showed remineralization potential (ie, ability to remineralize dentin in deep areas where the adhesives might fail to penetrate).…”
Section: Discussionmentioning
confidence: 99%
“… Adhesive system options including antiseptic molecules: Adhesive systems with 0.2% of CHX having anti-MMPs activities or including remineralizing modified calcium phosphate [ 40 , 54 , 55 ]. Adhesive systems with antibacterial monomer 12-methacryloyloxydodecylpyridinium bromide (MDPB): antibacterial activity based upon MDPB against S. mutans, L. casei and A. naeslundii, and the ability to disinfect cavities containing residual bacteria [ 54 , 56 , 57 ]. …”
Section: Therapeutic Options For Excavation and Tissue Conditioningmentioning
confidence: 99%
“…Adhesive systems with antibacterial monomer 12-methacryloyloxydodecylpyridinium bromide (MDPB): antibacterial activity based upon MDPB against S. mutans, L. casei and A. naeslundii, and the ability to disinfect cavities containing residual bacteria [ 54 , 56 , 57 ].…”
Section: Therapeutic Options For Excavation and Tissue Conditioningmentioning
confidence: 99%